2007
DOI: 10.1177/1359104507080981
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Investigation of Fathers' Experiences of Looking After a Child with a Life-limiting Illness, in Process and in Retrospect

Abstract: Child life-limiting illnesses are those from which there is no reasonable hope of cure and from which children will die. Only recently have these illnesses been recognized as a discrete category and thus relatively little research has focused specifically upon this group of children and their families. This study utilized qualitative methods to investigate the experience of fathers, a group who are often under-represented in child illness research. The research aim was to gain an understanding of fathers' expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(123 citation statements)
references
References 24 publications
6
116
0
1
Order By: Relevance
“…Fathers were as " in tune " with their children as mothers of children with chronic disease (23,29) . However, two articles noted that medical personnel speak primarily to females ahead of males, which further enhanced the father ' s sense of isolation (16,22) . In several interviews, fathers questioned the reinforcement of gender-based stereotypes as unhelpful when it came to the child ' s care.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fathers were as " in tune " with their children as mothers of children with chronic disease (23,29) . However, two articles noted that medical personnel speak primarily to females ahead of males, which further enhanced the father ' s sense of isolation (16,22) . In several interviews, fathers questioned the reinforcement of gender-based stereotypes as unhelpful when it came to the child ' s care.…”
Section: Resultsmentioning
confidence: 99%
“…Some fathers interviewed by Hayes and Savage (14) described becoming more stressed and upset than their wives. Ware and Raval (16) identified that their interviewees relied on socio-cultural norms of male expression and hence their ability to express emotions was, in some way, deficient. The study emphasized that, despite existing perceptions, fathers do want to talk about their child ' s illness.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations